Analysis of the Effect of Erythromycin Wastewater Degradation by Fenton Method - Chen, N.; Huang, L.J.; Liu, N.; Liu, Y.; Wang, S.F. (Asian Journal of Chemistry, 2013)
Erythromycin wastewater is a high chroma and concentration organic wastewater containing difficult biodegradable and more biologically toxic materials. In this paper, using Fenton method to pretreat erythromycin wastewater, analyzed the chemical compositions changes of wastewater before and after degradation. The experimental results showed that after treatment by Fenton method, removal rate of COD of wastewater was 40.88 %, sixteen-membered ring of erythromycin A was interrupted, macromolecules were degraded into eight kinds of smaller molecules, these substances caused high COD value and poor biodegradability of the effluent. This study aimed at providing certain theoretical basis for searching efficient treatment methods of erythromycin wastewater.